Legal Consequences of Polygyny Marriage Based on a Compilation of Islamic Law (Khi) and Laws on Marriage - ABDULLAH, Aisudin; WESNA, Putu Ayu Sriasih; UTAMA, I Wayan Kartika Jaya (Indonesia Strategic Sustainability, 2023)
The author conducted normative legal research by analyzing the consequences of polygynous marriage laws based on Islamic law. What is the focus of this research study? What are the criteria for not being able to carry out obligations and having a physical disability by Islamic Law and the Marriage Law? Moreover, what are the legal consequences of a judge's Decision at the Religious Court on requests for polygynous marriages? In this research, the law-based approach uses a case approach and a sociological approach. The criteria for not being able to carry out an obligation due to a physical disability are as intended in the Marriage Law and Islamic law, namely the inclusion of people with physical disabilities and people with mental disabilities. This is because the type of disability means that someone cannot carry out their obligations as husband or wife or by the provisions of marriage, especially people with physical disabilities. Related to people with physical disabilities, namely impaired movement functions such as amputated organs, paralysis, paraplegia, cerebral palsy, stroke, leprosy and others, which result in the inability to fulfill obligations by a person as a husband or wife as a basis for fulfilling physical and spiritual needs.